Decoupling the impact of bulk and surface point defects on the photoelectrochemical properties of LaFeO3 thin films. Issue 37 (16th September 2022) - Sun, Xin; Tiwari, Devendra; Li, Meicheng; Fermin, David J.
Abstract : This article shows, for the first time, the delicate balance between controlling bulk recombination sites and dynamics of interfacial carrier transfer via independently tuning the bulk and surface compositions of perovskite oxide thin films. Abstract : Point defects (PDs) play a key role in the properties of semiconductor photoelectrodes, from doping density to carrier mobility and lifetime. Although this issue has been extensively investigated in the context of photovoltaic absorbers, the role of PDs in photoelectrodes for solar fuels remains poorly understood. In perovskite oxides such as LaFeO3 (LFO), PDs can be tuned by changing the cation ratio, cation substitution and oxygen content. In this paper, we report the first study on the impact of bulk and surface PDs on the photoelectrochemical properties of LFO thin films. We independently varied the La : Fe ratio, within 10% of the stoichiometric value, in the bulk and at the surface by tuning the precursor composition as well as selective acid etching. The structure and composition of thin films deposited by sol–gel methods were investigated by SEM-EDX, ICP-OES, XPS and XRD. Our analysis shows a correlation between the binding energies of Fe 2p3/2 and O 1s, establishing a link between the oxidation state of Fe and the covalency of the Fe–O bond. Electrochemical studies reveal the emergence of electronic states close to the valence band edge with decreasing bulk Fe content. DFT calculations confirm that Fe vacancies generate states located near the valence band, which act as hole-traps and recombination sites under illumination. Dynamic photocurrent responses associated with oxygen reduction and hydrogen evolution show that the stoichiometric La : Fe ratio provides the most photoactive oxide; however, this can only be achieved by independently tuning the bulk and surface compositions of the oxide.